APPLICATION OF SULFONATED POLYSTYRENE IN POLYMER ELECTROLYTE FUEL CELL - Sunit Hendrana; Erwin Erwin; Krisman Krisman; Syakbaniah Syakbaniah; Isna’im Isna’im; Yusmeri Yusmeri; Neti Satria; Tri Susilawati; Sudirman Sudirman (Jurnal Sains Materi Indonesia, 2018)
APPLICATION OF SULFONATED POLYSTYRENE IN POLYMER ELECTROLYTE FUEL CELL. Sulfonated polystyrene (SPS) is polyelectrolyte solid that widely used in many aplications. In this works SPS is applied for some parts of polymer electrolyte fuel cell membrane due sulfonate group available in the structure. The investigation involve the application for membrane with addition of small molecules, i.e. benzimidazole and evaluating its microstructure and performance. Application of SPS solution as binding agent in MEA will also be presented.  The results show that when using SPS as fuel cell membrane, the additon of small molecules such as benzimidazole would modify its microstrusture as well as improve its ion conductivity. Meanwhile, some improvement still required for application of SPS solution as binding agent for preparation of Membrane Electrode Assembly or MEA.